Pressure comparative analysis study through the venturi pipe with the difference in diameter of the pipe. - Nurhayati, Nurhayati; Samita, Mauli; Harahap, Suryani (Phi: Jurnal Pendidikan Fisika dan Terapan, 2020)
The interesting phenomenon of a fluid flow in the venturimeter that has a different diameter of cappilaries pipe is that of a difference in fluid altitude, the velocity of flow in a pipe, as well as pressure. The study aims to analyze the relationship between the diameter of the capillaries pipe and the flow velocity, the height of the liquid and the pressure. The method in this research is experiment. After experiment, it is continued by calculating some variables using formulas and analyzing them. The conclution of this research is that if the diameter of the capillaries pipe is enlarged, the flow velocity becomes small, the level of the water's surface increases, and the pressure also increases. It corresponds to Bernoulli's equation.